Efficient hydrodeoxygenation of sulfoxides into sulfides under mild conditions using heterogeneous cobalt–molybdenum catalysts. Issue 1 (11th December 2019) - Yao, Kaiyue; Yuan, Ziliang; Jin, Shiwei; Chi, Quan; Liu, Bing; Huang, Renjie; Zhang, Zehui
Abstract : Nitrogen–doped carbon-supported cobalt–molybdenum bimetallic catalysts are active for the hydrodeoxygenation of sulfoxides to sulfides under mild conditions, which is the first case of use of heterogeneous non-noble metal catalysts for the reaction. Abstract : Nitrogen-doped carbon-supported cobalt–molybdenum bimetallic catalysts (abbreviated as Co–Mo/NC) are active for the hydrodeoxygenation of sulfoxides to sulfides under mild conditions (25–80 °C and 10 bar H2 ), which represents the first example of the use of heterogeneous non-noble metal catalysts for this transformation. MoO3 with Lewis acid sites assists the hydrodeoxygenation of sulfoxides into sulfides by hydrogen over cobalt nanoparticles.